Language learning strategies and self-efficacy of native ethnic pupils in learning English as a second language - Sigoh, Hellena Ak (2010)
This study is designed to document the use of language learning strategies among Year 5 ethnic pupils, their pattern of pupils' self-efficacy belief and the relationship of language learning strategies with self-efficacy pertaining to learning English as a second language. The data were collected using the questionnaires. The subjects comprised 251 Year 5 pupils from six national primary schools in Bintulu district. ANOVA, t-Test and Pearson Correlations were applied to analyse the data. The study finds that metacognitive strategies ranked the most preferred category of strategy used by native ethnic pupils and there is a significant difference in the use of metacognitive strategies between the boys and the girls. With regard to self-efficacy, the result shows that most pupils were of average level of self-efficacy and there is no distinct difference in children's level of self-efficacy. However, ethnicity does influence pupils' efficacy in learning English as a second language. Regarding the relationship between the language learning strategies and self-efficacy, the result reveals that there is a positive statistically significant relationship (p<0.01). It is proven that the use of particular strategies in learning English has positively correlated with the pattern of self-efficacy. Based on the findings and previous discussion on the implications for classroom instruction, the researcher has proposed few suggestions and recommendations which could improve the implementation of current primary school English Language curriculum as well as developing native ethnic pupils' language development. There are three practical curriculum agendas recommended in this study: (i) Alternative assessment (The Self-Assessment), (ii) Include specifications of language learning strategies in KBSR English Language curriculum and (iii) Conduct systematic and comprehensive needs analysis of native ethnic pupils of Sarawak